Allelism of IMP1 and GAL2 genes of Saccharomyces cerevisiae. - Donnini, C (1992)
Cloning and characterization of the previously described Saccharomyces cerevisiae IMP1 gene, which was assumed to be a nuclear determinant involved in the nucleomitochondrial control of the utilization of galactose, demonstrate allelism to the GAL2 gene. Galactose metabolism does not necessarily involve the induction of the specific transport system coded by GAL2/IMP1, because a null mutant takes up galactose and grows on it. Data on galactose uptake are presented, and the dependence on ATP for constitutive and inducible galactose transport is discussed. These results can account for the inability of imp1/gal2 mutants to grow on galactose in a respiration-deficient background. Under these conditions, uptake was affected at the functional level but not at the biosynthetic level.